2008
DOI: 10.1063/1.2901192
|View full text |Cite
|
Sign up to set email alerts
|

Localized surface plasmon assisted microfluidic mixing

Abstract: We present an optical microfluidic mixing approach via thermally induced convective flow sustained by localized surface plasmon ͑LSP͒ energy. The phonon energy associated with the nonradiative damping of LSP from a Au nanoparticle ͑NP͒ array under optical excitation creates a thermal gradient which initiates a convective fluidic flow. Experimental evidence and modeling results both show that LSP from the Au NPs is crucial in establishing a temperature gradient with sufficient magnitude to induce the convective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 12 publications
(8 reference statements)
0
48
0
Order By: Relevance
“…P lasmonic systems are drawing much attention due to their broad applications in several fields such as biology 1 , sensing 2 , nanoscale heating 3 , nonlinear optics 4,5 , optofluidics [6][7][8] and optical trapping [9][10][11][12][13][14] . Indeed, light-absorbing nanotextured surfaces such as those utilizing metal pads, dipole antennas and bowtie nanoantennas have recently been shown to be very effective for optical manipulation 9,13,15 .…”
mentioning
confidence: 99%
“…P lasmonic systems are drawing much attention due to their broad applications in several fields such as biology 1 , sensing 2 , nanoscale heating 3 , nonlinear optics 4,5 , optofluidics [6][7][8] and optical trapping [9][10][11][12][13][14] . Indeed, light-absorbing nanotextured surfaces such as those utilizing metal pads, dipole antennas and bowtie nanoantennas have recently been shown to be very effective for optical manipulation 9,13,15 .…”
mentioning
confidence: 99%
“…For instance, metal nanoparticles have been directly incorporated into or coated onto the channel material (e.g., poly(dimethylsiloxane)(PDMS)) to serve as surfaceenhanced Raman scattering substrates (Giesfeldt et al 2005), to enhance electrophoretic performance , to bind bio-molecular recognition elements (Luo et al 2005), and to develop immobilized enzyme reactors (Zhang et al 2008b). Furthermore, gold nanoparticles self-assembled on a substrate have been demonstrated for coupling of localized surface plasmon energy for thermal mixing (Miao et al 2008) and manipulation of bio-particles (Miao and Lin 2007a, b). Quantum dots (QDs) represent another promising technology for nano-engineered, microfluidic-based biosensing platform.…”
Section: Micro/nanofluidics Integrated With Nanobiosensorsmentioning
confidence: 99%
“…Such high‐intensity light may exceed the safety threshold of living tissues in bio/medical applications, which can cause some undesirable side effects, such as photodamage . Miao et al have demonstrated that the LSPR‐assisted photothermal effects enable microfluidic mixing at low optical power . By employing Au nanoparticle arrays on substrates, light with intensity as low as 6.4 × 10 3 W cm −2 has been used to generate the efficient convective flow for fluid mixing ( Figure ).…”
Section: Plasmon‐enhanced Functionalities In Microfluidicsmentioning
confidence: 99%